2004
DOI: 10.1007/s11661-006-0217-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of martensite morphology and tempering on dynamic deformation behavior of dual-phase steels

Abstract: The effects of martensite morphology and tempering on the quasistatic and dynamic deformation behavior of dual-phase steels were investigated in this study. Dynamic torsional tests were conducted on six steel specimens, which had different martensite morphologies and tempering conditions, using a torsional Kolsky bar, and then the test data were compared via microstructures, tensile properties, and fracture mode. Bulky martensites were mixed with ferrites in the step-quenched (SQ) specimens, but small martensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 30 publications
(29 reference statements)
2
33
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] They have attracted considerable attention in the automotive industry in recent years due to their superior formability and high strength to weight ratio. [8][9][10][11][12][13][14] Dual-phase steels are processed to a composite microstructure with interesting mechanical properties such as continuous yielding, low yield stress to tensile strength ratios, high initial work-hardening rate, high strength, and good ductility. This microstructure is comprised primarily of a relatively soft ferrite matrix and hard martensite particles, although it may contain other constituents (retained austenite, bainite, and pearlite).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] They have attracted considerable attention in the automotive industry in recent years due to their superior formability and high strength to weight ratio. [8][9][10][11][12][13][14] Dual-phase steels are processed to a composite microstructure with interesting mechanical properties such as continuous yielding, low yield stress to tensile strength ratios, high initial work-hardening rate, high strength, and good ductility. This microstructure is comprised primarily of a relatively soft ferrite matrix and hard martensite particles, although it may contain other constituents (retained austenite, bainite, and pearlite).…”
Section: Introductionmentioning
confidence: 99%
“…[21] It seems that different failure mechanisms (void nucleation and growth) of particular DP steels may be related to their chemical compositions, history of heat treatment, and differences of their final microstructure. [4,[6][7][8][9]11,12,[16][17][18][19][20][22][23][24][25][26][27][28][29][30][31] Significant plastic deformation of martensite occurs when its strength is reduced either by carbon content or by tempering. With respect to void nucleation, such as martensite cracking, Stevenson [30] reported that voids could be mainly nucleated by cracking of martensite islands.…”
Section: Introductionmentioning
confidence: 99%
“…It further accelerates localized shear deformation at the gage center, which reduces the load carrying capacity of the central area, thereby leading to a rapid decrease of shear stress in shear stress-shear strain curves and final fracture. [27][28][29][30] Adiabatic shear bands are frequently found in materials having low strain hardenability, low strain rate sensitivity, low thermal conductivity, and high thermal softening rate. [23][24][25] Dynamic torsional deformation of ductile metals develops in the following three stages: (1) homogeneous deformation stage before reaching maximum shear stress, (2) inhomogeneous deformation stage starting from the maximum shear stress point, and (3) initiation and development stage of an adiabatic shear band due to shear localization.…”
Section: Discussionmentioning
confidence: 99%
“…[12,23] It plays a role in initiating a partial or total fracture, which is not desirable in the perspective of the fracture resistance under dynamic loading. [12,23,[27][28][29] Consequently, it is desirable to prevent the formation of adiabatic shear bands by the microstructural control through alloy design or heat treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This correlates to the absence of brittle features on the fracture surface, aside from inclusions, with the predominance of ductile dimple rupture in tensile or shear mode and localized shear failure in the fissures. There have been other fractography investigations of DP and TRIP steels that have observed regions of cleavage facets, [25][26][27][28][29] but also studies [30][31][32][33][34][35] where the entire fracture surface consists of dimples. This study's observations correspond with those of the latter, such that either the ruptured martensite also exhibits ductile dimples or the fracture surface only results from the rupture of the ferrite matrix.…”
Section: B Correlation To Mid-plane and Fracture Surface Analysesmentioning
confidence: 99%